Crystal structure of (E)-7-fluoro-2-(4-methoxy-2-(trifluoromethyl)benzylidene)-3,4-dihydronaphthalen-1(2H)-one, C19H14F4O2 - Meng Qing-Guo; Zhao Sheng-Nan; Sun Zhong-Hao; Shan Guang-Zhi; Meng Qing-Guo (Zeitschrift für Kristallographie - New Crystal Structures)
C19H14F4O2, monoclinic, P21/c (no. 14), a = 11.8614(10) Å, b = 7.9148(6) Å, c = 16.7999(16) Å, β = 99.150(9)°, V = 1557.1(2) Å3, Z = 4, R gt(F) = 0.0446, wR ref(F 2) = 0.1150, T = 100 K.